TEACHING SKILLS FOR THE ENGLISH LANGUAGE THROUGH TRADITIONAL VISUAL METHODS - RAMAKR ISHNA GODDETI,TELUGU PARUSU RAMUDU, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The English language plays a major role in every person's life whoever wants to achieve in their professional like. It is a challenge to master this language to any non native speaker. Globally , lot of innovative methodologies are bring adapted to enrich this language learning. This paper focuses on the English language teaching through the traditional visual media. The techniques that are used for ages to develop and reading skills are discussed